ANALISIS PERKEMBANGAN AKTIVITAS KESUSASTRAAN KOMUNITAS ONLINE LEKO KUPANG PERIODE 2020/2021 - Zianet, Maria Katharina (Jurnal Dinamika Sosial Budaya, 2022)
Abstract Discussed about the literary activities of the online community, named LEKO Kupang. Literary activities or literature in question are more for the learning process in creating, writing, reading, appreciating, criticizing, and reviewing various literary literatures. Departing from the community profile which becomes a kind of general indicator in explaining and describing all forms of the process of developing literary activities. So, based on these indicators, several topics were found, such as the structure and coordination system of the LEKO Kupang online community, the development of activities (programs or activities) of the LEKO Kupang online community as of the 2020/2021 period. Empowerment of community facilities, namely Fanu Bookstore as a follow-up to the activities of the literary community, and to the elaboration of the problem tree and purpose tree of the community. From the discussion points, it is certain that the development activities of the online community LEKO Kupang refer to problems and/or problems related to the structural and geographical aspects of the community. Keywords: Development, Literature, Online Community, LEKO Kupang. Abstrak Penulisan yang membahas tentang aktivitas kesusastraan dari komunitas online LEKO Kupang. Aktivitas sastra atau kesusastraan yang dimaksud lebih kepada proses belajar dalam menciptakan, menulis, membaca, mengapresiasi, mengkritik, serta mengkaji berbagai literatur sastra. Berangkat dari profil komunitas yang menjadi semacam indikator umum dalam menjelaskan dan menggambarkan segala bentuk proses perkembangan aktivitas kesusastraan. Maka, berdasarkan indikator-indikator tersebut, ditemukan beberapa pokok bahasan seperti struktur dan sistem koordinasi komunitas online LEKO Kupang, perkembangan aktivitas (program atau kegiatan) komunitas online LEKO Kupang per periode 2020/2021. Pemberdayaan fasilitias komunitas, yakni toko buku Fanu sebagai tindak lanjut dari aktivitas kesusastraan komunitas, dan sampai pada penjabaran tentang pohon masalah dan pohon tujuan dari komunitas. Dari pokok-pokok pembahasan tersebut, dapat disimpulkan bahwa perkembangan aktivitas kesusastraan komunitas online LEKO Kupang merujuk pada problematika dan atau penyelesaian masalah terkait aspek struktural dan aspek geografis dari komunitas tersebut. Kata Kunci: Perkembangan, Kesusastraan, Komunitas Online, LEKO Kupang.